Strut-and-tie models for deteriorated reinforced concrete half-joints. (15th April 2018) - Desnerck, Pieter; Lees, Janet M.; Morley, Chris T.
Highlights: STM provisions are discussed in the context of assessments. Twelve different reinforced concrete half-joint scenarios are tested. For studied specimens the STM predictions were compared to the test results. STM methods lead to safe predictions of the failure load. STM were, however, unable to pick up alternative load path development. Abstract: A reinforced concrete half-joint bridge consists of suspended span dapped-end beams or a full-width deck supported on the nibs of abutments or adjacent beams. The design of their disturbed regions is traditionally performed by means of strut-and-tie modelling. The design provisions found in standards and codes can be used for the assessment of existing structures with minor adjustments. However, current documents provide limited guidance on the incorporation of deterioration aspects such as corrosion, insufficient anchorage lengths, and crack formation. Experiments performed on 12 half-joint beams demonstrated the effects of single defects, but synergistic effects were also found to exist and might lead to much higher reductions than expected from the sum of individual defects. These results were compared to different strut-and-tie models (STMs) and the application of STMs to achieve the highest lower bound estimate of the load carrying capacity is discussed. For the beams studied in the current work, the predictions based on codes and standards, combined with appropriate methods to incorporate deterioration effects, led to safe load bearing capacity estimates. However, the developed STMs seem to be, in some instances, unable to pick up alternative load paths that develop as soon as the capacity of a certain tie is reached. Hence the actual capacities might be higher than what is obtained from the STM calculations.